Penggunaan Geogebra untuk Meningkatkan Pemahaman Konsep Kesebangunan : Analisis Bibliometrik - Najma Ulya; Hasanuddin Hasanuddin (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the trends and development of research related to the use of Geogebra in improving the understanding of the concept of revival with a bibliometric approach. Data was collected from the Google Scholar database using the Publish or Perish (PoP) application in the 2020-2025 time span. The initial identification results found 393 documents, which were then filtered to obtain 11 documents worthy of analysis. The analysis was conducted with the help of VOSviewer software to map keywords, annual trends, and research topic density. The results showed that the number of publications increased significantly since 2021, with peaks in 2022 and 2023. Network, overlay, and density visualizations show that the topic of Geogebra usage is growing and diversifying, with a focus on interactive learning models, student abilities, and visual understanding of the concept of congruence. This research makes an important contribution to literature mapping and opens up opportunities for further research in the field of mathematics education technology.